The Phylogenetic Analysis of Cimex hemipterus (Hemiptera: Cimicidae) Isolated from Different Regions of Iran Using Cytochrome Oxidase Subunit I Gene - Awat Samiei; Mousa Tavassoli; Karim Mardani (Tehran University of Medical Sciences, 2020)
Background: Bedbugs are blood feeding ectoparasites of humans and several domesticated animals. There are scarcity of information about the bed bugs population throughout Iran and only very limited and local studies are available. The aim of this study is to assess the phylogenetic relationships and nucleotide diversity using partial sequences of cytochrome oxidase I gene (COI) among the populations of tropical bed bugs inhabiting Iran. Methods: The bedbugs were collected from cities located in different geographical regions of Iran. After DNA extraction PCR was performed for COI gene using specific primers. Then DNA sequencing was performed on PCR products for the all 15 examined samples. Results: DNA sequencing analysis showed that the all C. hemipterus samples were similar, despite the minor nucleotide variations (within the range of 576 to 697bp) on average between 5 and 10 Single nucleotide polymorphisms (SNPs). Subsequently, the results were compared with the database in gene bank which revealed close similarity and sequence homology with other C. hemipterus from other parts of the world. Conclusion: In conclusion, this study has demonstrated the ability of the COI gene to differentiate between the C. hemipterus populations from a few different locations in Iran. The current research is the first report of phylogenetic and genetic species diversity analysis conducted on C. hemipterus in Iran. These results provided basic information for further studies of molecular epidemiology, public health and pest control operators in Iran.